Preliminary in vitro assessment of the potential toxicity and antioxidant activity of Ceiba speciosa (A. St.-Hill) Ravenna (Paineira) - Camila Krüger Cardoso Malheiros; Joyce Sayonara Barbosa Silva; Tânia Cristiane Hofmann; Thiane Martins Messina; Vanusa Manfredini; Jacqueline da Costa Escobar Piccoli; Débora Faoro; Luís Flávio Souza Oliveira; Michel Mansur Machado; Fabiane Moreira Farias (Universidade de São Paulo, 2017)
ABSTRACT The bark tea of Ceiba speciosa, a tropical tree of the Malvaceae family, is used in the Northwestern Region of Rio Grande do Sul state, Brazil, to reduce blood cholesterol levels. However, there are no scientific data on the efficacy and safety of this plant. The aim of the present study was to evaluate the in vitro antioxidant and toxic potential of bark extracts of C. speciosa. We performed a preliminary phytochemical analysis by high-performance liquid chromatography-diode array detection (HPLC-DAD) and evaluated the oxidative damage to proteins and lipids, the radical scavenging effect, and genotoxicity of the lyophilized aqueous extract (LAECs) and the precipitate obtained from the raw ethanol extract (Cs1). The phytochemical proﬁle demonstrated the presence of phenolic and ﬂavonoid compounds. The LAECs and Cs1 prevented damage to lipids and proteins at concentrations of 50 and 10 µg/mL. They also showed a scavenging effect on 2,2-diphenyl-1-pricril-hydrazyl (DPPH) radicals in a concentration-dependent manner. Furthermore, no genotoxic effect was observed at concentrations of 10, 5 and 2 µg/mL in the Comet assay. The present study is the first evaluation regarding the characterization of C. speciosa and its safety, and the results demonstrate its antioxidant potential and suggest that its therapeutic use may be relatively safe.